Coaches` interpersonal emotion regulation and the coach-athlete relationship - Braun, C.; Tamminen, K. A. (Movement & Sport Sciences - Science & Motricité, 2019)
Researchers have examined the impact of coaches` emotional expressions and emotional intelligence on athlete outcomes (Allan, V., & Côté, J. (2016). A cross-sectional analysis of coaches` observed emotion-behavior profiles and adolescent athletes` self-reported developmental outcomes. Journal of Applied Sport Psychology, 28, 321-337; Thelwell, R.C., Lane, A.M., Weston, N.J., & Greenlees, I.A. (2008). Examining relationships between emotional intelligence and coaching efficacy. International Journal of Sport and Exercise Psychology, 6, 224-235; van Kleef, G.A., Cheshin, A., Koning, L.F., & Wolf, S.A. (2018). Emotional games: How coaches` emotional expressions shape players` emotions, inferences, and team performance. Psychology of Sport & Exercise). However, there is little research examining coaches` use of specific strategies to regulate their athletes` emotions. The purpose of the present study was to explore the strategies coaches used to try and regulate their athletes` emotions, and to explore the relationship and contextual factors influencing coaches` IER strategy use. A longitudinal multiple case study approach was used (Stake, R.E. (2006). Multiple case study analysis. New York: The Guilford Press) with five cases, each consisting of one male coach and two individual varsity sport athletes (N?=?15). Participants completed individual interviews, a two-week audio diary period, and a follow-up interview. Data were inductively and deductively analyzed and a conceptual model was developed outlining athletes` emotions and emotion regulation, coaches` IER, the coach-athlete relationship, and contextual factors. Participants described a bidirectional association between the coach-athlete relationship and coaches` IER. A number of factors influenced athletes` and coaches` use of emotion regulation strategies and contributed to the quality of the coach-athlete relationship. The IER strategies that coaches used may reflect instrumental, performance-related motives, and coaches` IER efforts may also contribute to coaches` emotional labour.